High-resolution structure of monomorphic Aβ 1-40 fibrils - Salima Bahri; Ravi Shankar Palani; Robert Silvers; Brian Michael; Veronica Lattanzi; Ingemar André; Sara Linse; Robert G. Griffin (Proceedings of the National Academy of Sciences, 2026)
Amyloid-β (Aβ) fibrils primarily composed of Aβ 1-40 and Aβ 1-42 form the core of senile plaques in Alzheimer’s disease. Aβ 1-40 fibrils may exhibit significant polymorphism influenced by sample preparation conditions, complicating atomic resolution structural characterization. To establish a reliable structural baseline, we developed a protocol for expressing and purifying recombinant Aβ 1-40 that forms monomorphic fibrils under physiological conditions (pH 7.4). We present a high-resolution structure of these unseeded, monomorphic Aβ 1-40 fibrils obtained using magic-angle spinning NMR spectroscopy (PDB ID 12GB). We obtained unambiguous chemical shift assignments for approximately 90% of the residues and measured over 500 distance and torsion angle restraints. The resolved structure, with a backbone RMSD of 0.63 ± 0.06 Å, shows two monomers per filament plane, with two distinct β-sheets (residues E11-E22 and K28-V39, respectively) running along the fibril axis with H-bonding between each plane, and the two strands linked by a flexible loop region. This structure reveals three continuous hydrophobic cores inside each filament which bury 24 hydrophobic side chains per filament plane: those of L17, F19, A21, V24, A30, I32, M35, V40 between the two β-strands within each monomer and I31, L34, V36, V39 between the two monomers. Small angle X-ray scattering reveals the size and geometry of the fibril cross-section, which is compatible with a two-filament arrangement with a total of 4 monomers per fibril plane.